Swedish Youths as Listeners of Global Englishes Speakers With Diverse Accents: Listener Intelligibility, Listener Comprehensibility, Accentedness Perception, and Accentedness Acceptance - Jeong, Hyeseung; Elgemark, Anna; Thorén, Bosse (Frontiers in Education, 2021)
As reflected in the concept of Global Englishes, English mediates global communication, where English speakers represent not merely those from English-speaking countries like UK or US but also global people from a wide range of linguistic backgrounds, who speak the language with diverse accents. Thus, to communicate internationally, cultivating a maximized listening proficiency for and positive attitudes toward global Englishes speakers with diverse accents is ever more important. However, with their preference for American English and its popular culture, it is uncertain whether Swedish youth learners are developing these key linguistic qualities to be prepared for the globalized use of English. To address this, we randomly assigned 160 upper secondary students (mean age = 17.25) into six groups, where each group listened to one of six English speakers. The six speakers’ first languages were Mandarin, Russian/Ukrainian, Tamil, Lusoga/Luganda, American English, and British English. Through comparing the six student groups, we examined their listener intelligibility (actual understanding), listener comprehensibility (feeling of ease or difficulty), accentedness perception (perceiving an accent as native or foreign), and accentedness acceptance (showing a positive or negative attitude toward an accent) of diverse English accents. The results showed that the intelligibility scores and perception/attitude ratings of participants favored the two speakers with privileged accents – the American and British speakers. However, across all six groups, no correlation was detected between their actual understanding of the speakers and their perception/attitude ratings, which often had a strong correlation with their feelings of ease/difficulty regarding the speakers’ accents. Taken together, our results suggest that the current English education needs innovation to be more aligned with the national syllabus that promotes a global perspective. That is, students need to be guided to improve their actual understanding and sense of familiarity with Global English speakers besides the native accents that they prefer. Moreover, innovative pedagogical work should be undertaken to change Swedish youths’ perceptions and attitudes and prepare them to become open-minded toward diverse English speakers.